The Development of Flashcard Media to Teach Vocabulary on English Material in 7th Grade Junior High School - Amalia, Leny Leny; Rofi'ah, Siti; Saifudin, Ahmad (Jurnal Pembelajaran dan Ilmu Pendidikan, 2025)
This research focused on developing flashcard-based learning media to support vocabulary improvement among seventh-grade students at MTs Nurul Huda Ngadirejo. The development followed the ADDIE model, which includes the phases of Analysis, Design, Development, Implementation, and Evaluation. It responded to key issues identified in the needs analysis, such as students limited vocabulary and low engagement caused by traditional teaching methods. The flashcards incorporated visual features and contextualized vocabulary to enhance both memory retention and student interest. Expert validation rated the media as “Good” with a score of 80%, confirming its appropriateness for use. Reliability testing yielded a Cronbach’s Alpha of 0.956, indicating a high level of internal consistency. Student satisfaction reached 80.92% in the “Very Good” category, particularly noting the media’s visual appeal, motivational impact, and support for vocabulary retention. Revisions based on expert feedback helped improve the final product. In conclusion, the flashcard media proved to be an effective and engaging tool for vocabulary instruction, offering a viable option for wider classroom application.